Consumers’ Perceived quality of Restaurants in Nueva Ecija - Vigilia, Aileen Y. (International Journal of Humanities and Education Development (IJHED), 2020)
Some determinants of customer satisfaction are the physical environment and the interactional quality of restaurants. This paper assessed the quality of restaurants in terms of physical environment quality, interactional quality and outcome quality of restaurants. A total of 29 restaurants (18 fast food restaurants and 11 fine dining restaurants) were surveyed used an adapted questionnaire with likert-scale responses. In lieu of the foregoing discussions, the researcher had drawn three conclusions. First, restaurants provide physical environment quality in terms of ambient condition, spatial layout, and seating comfort. It is implied that customers were considering the physical conditions of a restaurant in its provision of comfort to customers. Hence, it is recommended to regulate the temperature inside the restaurant and review the signage boards to avoid confusion of customers. Second, restaurants provide interactional quality in terms of assurance, empathy, reliability and responsiveness. It is implied that customers were observant to the servers of the restaurant which yields customer satisfaction. Hence, it is recommended that restaurants should improve the speed of service to raise its interactional quality. Third, restaurants provide outcome quality in their menu and served foods. It is implied that customers seek for variety in the menu and quality food to ease their cravings. Hence, it is recommended that restaurants should add variety of foods so customers will have more options to choose from.